PENGARUH PENDEKATAN CTL (CONTEXTUAL TEACHING AND LEARNING) TERHADAP HASIL BELAJAR MEMBACA PEMAHAMAN BAHASA INDONESIA SISWA KELAS IV SD - Noor Alfu Laila (Jurnal Cakrawala Pendidikan, 2009)
AbstractEffects of the Contextual Teaching and Learning Approach on the LearningAchievement in Indonesian Language Reading Comprehension of Year IV Studentsof Elementary Schools. This study aims to investigate effects of the ContextualTeaching and Learning (CTL) approach on learning achievement in Indonesianlanguage reading comprehension of groups of students based on their learningmotivation. This study was an experimental study employing a 2x2 factorialdesign. The independent variable had two levels, i.e. the CTL approach and theconventional approach. The population comprised all 61 Year IV students of SDNSidoarum and SDN Krapyak. The instruments consisted of an achievement test anda learning motivation questionnaire. The data were analyzed by means of a twowayANOVA and the Scheffe test. The results show that (1) there is a difference inlearning achievement between the students in the experimental group and those inthe control group, (2) there is a difference in learning achievement betweenstudents with high motivation in the experimental group and those in the controlgroup, (3) there is a difference in learning achievement between students with lowmotivation in the experimental group and those in the control group, (4) the CTLapproach is more effective than the conventional approach, and (5) there is nointeraction between approaches and learning motivation.Keywords: learning achievement in reading comprehension, CTL approach,learning motivation